2013
DOI: 10.1097/ss.0000000000000011
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Different Carbon Management Strategies on Water Flow and Related Processes for Three Loamy Soils

Abstract: The decline in organic matter of arable land, induced and accelerated by modern agriculture, has been identified as a threat to sustained soil quality. In this article, we studied strategies to counter this decrease by building up soil organic carbon (SOC) levels in the soils using several approaches. They included return of organic matter, such as straw, animal manure, and slurry, to the soil and diverse crop rotations with, for example, grass-clover leys. We used three field sites in Denmark with different C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…However, the difference in the shape of the EC curves (i.e., the later peak in EC) might be seen as an indication that the CMA and CHA treatments exhibit a larger degree of lateral mass transfer compared with the U, CS, and SA treatments. Previous studies analyzing relations between either SOM or clay/OC (Dexter) ratio and 5% mass recovery of 3 H 2 O at free drainage conditions did not find significant correlations between the soil C parameters and early tracer breakthrough Soares et al, 2015;Vendelboe et al, 2013). This is in accordance with the present study in which a wide range in the clay/OC ratio did not affect either early tracer breakthrough or mass recovery in general.…”
Section: Treatment Colloid Concentrationsupporting
confidence: 91%
“…However, the difference in the shape of the EC curves (i.e., the later peak in EC) might be seen as an indication that the CMA and CHA treatments exhibit a larger degree of lateral mass transfer compared with the U, CS, and SA treatments. Previous studies analyzing relations between either SOM or clay/OC (Dexter) ratio and 5% mass recovery of 3 H 2 O at free drainage conditions did not find significant correlations between the soil C parameters and early tracer breakthrough Soares et al, 2015;Vendelboe et al, 2013). This is in accordance with the present study in which a wide range in the clay/OC ratio did not affect either early tracer breakthrough or mass recovery in general.…”
Section: Treatment Colloid Concentrationsupporting
confidence: 91%
“…However, the effects of SOC per se on solute transport in arable soil have hardly been investigated and are not well understood. The results from two earlier studies that attempted to address this question were inconclusive (Vendelboe et al, 2013; Soares et al, 2015), probably because the range of variation in SOC content (17–22 g kg −1 ) was too small. Other studies performed at the field and catchment scales for a limited number of soil columns have suggested that preferential transport may be weaker in conventionally tilled arable topsoils with larger SOC content (Jarvis et al, 2007; Ghafoor et al, 2013; Paradelo et al, 2016).…”
mentioning
confidence: 98%
“…Preferential flow can occur readily during both near-saturated and unsaturated conditions (e.g. de Jonge et al, 2004;Rosenbom et al, 2008;Vendelboe et al, 2013), allowing water to bypass the soil matrix and its retarding effect (degradation and sorption), and providing a direct pathway to drainage and groundwater (Jarvis, 2007), which may increase leaching of pesticides and their degradation products, such as TFMP. Kjaer et al (2005) found preferential flow occurring within a short time of application of glyphosate to be the governing factor for glyphosate leaching, and Rosenbom et al (2014) found that MCPA only leaches out of the root zone if preferential flow occurs.…”
Section: Resultsmentioning
confidence: 99%